y+2=0.6(x-1)

Simple and best practice solution for y+2=0.6(x-1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for y+2=0.6(x-1) equation:


Simplifying
y + 2 = 0.6(x + -1)

Reorder the terms:
2 + y = 0.6(x + -1)

Reorder the terms:
2 + y = 0.6(-1 + x)
2 + y = (-1 * 0.6 + x * 0.6)
2 + y = (-0.6 + 0.6x)

Solving
2 + y = -0.6 + 0.6x

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-2' to each side of the equation.
2 + -2 + y = -0.6 + -2 + 0.6x

Combine like terms: 2 + -2 = 0
0 + y = -0.6 + -2 + 0.6x
y = -0.6 + -2 + 0.6x

Combine like terms: -0.6 + -2 = -2.6
y = -2.6 + 0.6x

Simplifying
y = -2.6 + 0.6x

See similar equations:

| 5x+10y-12z=0 | | 9x+2-5x=10+3x+1 | | 1.25v+16=.833v+14 | | -(1-0)+3= | | x+3x+9-5x=180 | | 6m(m+3n+1)= | | 79-x=40 | | y=mx+bwhatism | | 6t^2-2t+2=4t^2 | | (7w-4)-(w+3)= | | 3y+5=5y-3y | | -(1-0)3= | | X^2+15-16=0 | | 2(18+-6y)-3y=-24 | | 5n+8=-(2-6n)+8 | | 3xsquared=6-9x | | 8x+12+9(2x-4)= | | 5z-0.6=6z | | -3=a(3-0)-4 | | -3u-1/3u=1/4-7/3 | | (8n-1)+(4n+5)= | | 7y(4y-2)= | | -4ac-5b= | | 2lnx-6=12 | | 3x-20x-7=0 | | x-9+x+5x=180 | | 3=a(3-0)-4 | | -2(7x-4)+6(5x+1)= | | 7x-1-9x+5= | | 4(6x-4)+5(15-3x)-4(2x+3)=-2 | | (x+3)+2x+x=23 | | 3x*3x*3x+4=31 |

Equations solver categories